Interlab: Interactive Technologies Laboratory - Tori, Romero; Nakamura, Ricardo; Nunes, Fátima; Bernardes Jr., João Luiz; Ferreira, Maria Alice; Ranzini, Edith (Journal on Interactive Systems, 2011)
<!– p, li white-space: pre-wrap; –> <!–StartFragment–>In this paper we present an overview of Interlab, including its origin, research lines and some of the ongoing projects.